(untitled) (Actualizaciones en Sida e Infectología, 2022)
Main objective. To determine the adherence to hand washing in health care staff in pre-pandemic and covid-19 pandemic periods, after intensifying the measures of a program. Secondary objectives. Determine adherence according to professional category, hospitalization sectors and moments of hand washing. Methodology. Quasi-experimental study that evaluated adherence to hand washing before and after intensifying measures. The adherence of 2 periods was compared, December 2019 and August 2020. Outcomes. It was observed that adherence in 2019 was 67% (95% IC: 63% -71%) and in 2020 it was 89% (95% IC: 86% -92%), which implies an increase of 22% (95% IC: 0.17-0.27; p: 0.000). In the subgroup analysis of WHO moments, an increase was observed in the moments grouped as before (65.7 to 81.2; p: 0.001) and as after (67.7 to 94.3; p: 0.000). In the analysis by hospitalization sectors, an increase was observed in emergency sectors (50.5 to 100; p: 0.000) and hospitalization (63.3 to 78.0; p: 0.006) and not significant in pediatrics (94.2 to 96.5; p : 0.336) and UTI / UCO (63.7 to 70.5; p: 0.405). In the analysis by professional category, a significant increase was observed in the categories nurse (81.4 to 92.9; p: 0.001), doctors (66.7 to 83.8; p: 0.003), technicians (57.8 to 93.2; p: 0.000) and support (49.4 to 83.9; p: 0.000). Conclusion. In our study, the intensification of hand washing measures and the pandemic led to a significant increase in adherence to hand hygiene.